Trend Publication of Computational Thinking in Mathematics Education: Bibliometric Review - Maharani, Swasti; Susanti, Vera Dewi; Andari, Tri; Krisdiana, Ika; Astuti, Indra Puji (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2023)
Computational thinking and mathematics are closely related, namely mathematics plays a role in overcoming challenges and understanding concepts in computational thinking, while computational thinking ultimately simplifies and abstracts situations by formulating and presenting problems in mathematical form. The purpose of this study is to identify trends and research patterns with the topic of computational thinking in mathematics education using bibliometric analysis. Data is obtained from the dimensions database which has been refined through 4 stages (identification, screening, eligibility, and inclusion). The results showed that the peak of publications related to computational thinking in mathematics education research occurred in 2022. The Journal of Science of Education and Technology became the most influential journal with the most citations, namely 877 citations even though it only with 7 publications. The United States is the most influential country in this field because of the good number of publications, the number of citations is the highest of any other country. There are three research focuses related to computational thinking in mathematics education research on the dimensions database from 2013-2023, namely, 1) mathematics, study, teacher; 2) problem, child, learning; 3) student, steam, CT skill